2015
DOI: 10.1007/s10529-015-2019-6
|View full text |Cite
|
Sign up to set email alerts
|

Morphology engineering of basidiomycetes for improved laccase biosynthesis

Abstract: ObjectiveThis work is the first application of a morphological engineering technique called microparticle-enhanced cultivation (MPEC) aimed at the facilitation of laccase production in the submerged cultures by two basidiomycetes species Cerrena unicolor and Pleurotus sapidus.ResultsThe positive effect of the applied 10 μm Al2O3 microparticles at concentrations from 5 to 30 g Al2O3 l−1 was shown. Laccase activity increased 3.5-fold for C. unicolor and 2-fold for P. sapidus at 15 g Al2O3 l−1 on 9 and 14 day of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 14 publications
0
38
0
Order By: Relevance
“…The second most popular microparticle is aluminum oxide, which proved to be completely insoluble in water and inactive (Etschmann et al 2015 ). Results of other authors confirmed that the most effective aluminum oxide concentration is similar to that of talc, approximately 15–20 g l −1 (Driouch et al 2010a , b ; Etschmann et al 2015 ; Coban et al 2015a ; Antecka et al 2016 ).…”
Section: Microparticle-enhanced Cultivation Of Filamentous Fungimentioning
confidence: 69%
See 4 more Smart Citations
“…The second most popular microparticle is aluminum oxide, which proved to be completely insoluble in water and inactive (Etschmann et al 2015 ). Results of other authors confirmed that the most effective aluminum oxide concentration is similar to that of talc, approximately 15–20 g l −1 (Driouch et al 2010a , b ; Etschmann et al 2015 ; Coban et al 2015a ; Antecka et al 2016 ).…”
Section: Microparticle-enhanced Cultivation Of Filamentous Fungimentioning
confidence: 69%
“…Also for organisms of the genus Aspergilli MPEC led to the increase of product formation: 4-fold higher of α-glucoamylase and β-fructofuranosidase secretion by A. niger (Driouch et al 2010a ), a 3.5-fold higher lovastatin titer produced by A. terreus ATCC 20542 (Gonciarz et al 2016 ) or a 3-fold increase of phytase activity by A. ficuum NRRL 3135 (Coban et al 2015a ). The latest study also proved the positive effect of microparticles for basidiomycetes strains (Antecka et al 2016 ). Despite the fact that fungal morphology for C. unicolor and P. sapidus were completely different, in both cases laccase activity was increased, 3.5 and 2-fold, respectively.…”
Section: Microparticle-enhanced Cultivation Of Filamentous Fungimentioning
confidence: 90%
See 3 more Smart Citations